The concept and legal nature of the institution of withdrawal in the economic process under the legislation of Uzbekistan - Ibratova Feruza; Sobirova Muslimakhon (Periodica Journal, 2025)
The article examines the essence of the institution of recusal in economic proceedings, the grounds and mechanism of its application to the judge and other participants in the case, and also identifies existing problems and prospects for the development of this institution in the context of the current stage of development of economic proceedings in the Republic of Uzbekistan.
Keywords: proceedings; essence; recusal